Religious Character Formation Through Habituation of Worship Activities: Pembentukan Karakter Religi Melalui Pembiasaan Kegiatan Ibadah - Rahmawaty, Milla; Supriyadi, Supriyadi (Indonesian Journal of Islamic Studies, 2025)
Background: Religious character education in elementary school is crucial to counter negative influences from the rapid flow of information in today’s digital era. Specific Background: SDN Lemahputro 1 Sidoarjo shows low levels of students’ religious character internalization, prompting the need for effective strategies. Gap: Few studies explore how daily habituation of religious activities in elementary schools fosters consistent character formation. Aim: This research aims to describe how religious character values are internalized through habituation of worship activities. Method: A qualitative case study was conducted using interviews, observations, and documentation with teachers, principals, and parents. Results: The findings reveal that religious character formation is supported through regular dhuha prayer, istighosah, infaq practice, and reading short Qur’anic surahs. These activities cultivate discipline, cooperation, and spiritual awareness among students. Novelty: This study highlights a structured model of religious habituation that integrates school, teacher, and parental involvement. Implications: The results provide a reference for schools to design consistent religious habituation programs to strengthen students’ moral and spiritual development. Highlights : Daily worship routines strengthen students’ religious character Collaboration between teachers and parents enhances habituation Religious habituation fosters discipline and social care KeywordReligious Character, Elementary School, Habituation, Dhuha Prayer, Infaq